Modified ZhuJing pill protects retinal pigment epithelium against oxidative stress-induced epithelial–mesenchymal transition through Nrf2-mediated Akt/GSK3β pathway - Yang, Ning; Xiong, Caijian; Feng, Siqi; Gao, Mengqi; Zhou, Siqi; Hui, Qinyi; Zhou, Xin; Jin, Qingzi; Shao, Yan; Xu, Xinrong (Frontiers in Pharmacology, 2025)
BackgroundThe modified ZhuJing pill (mZJP) has been widely used in China as a classical prescription for treating retinal diseases for years. Our preliminary experiment showed that mZJP exerted an antioxidant effect in treating dry age-related macular degeneration (AMD). Nevertheless, the specific mechanism underpinning the impact of mZJP on dry AMD remains obscure.MethodsThe chemical metabolites of mZJP were qualitatively analyzed using LC-Q-TOF-MS. Dry AMD model mice were used to assess the efficacy of mZJP through optical coherence tomography (OCT), fundus autofluorescence (FAF), and immunofluorescence. Epithelial–mesenchymal transition (EMT) in OxLDL-induced ARPE-19 cells was evaluated by monitoring cellular integrity and quantifying EMT-related markers. Cell migration capacity was determined via wound healing and transwell assays. To investigate molecular mechanisms, cells were transfected with Nrf2 siRNA and analyzed through Western blotting, immunofluorescence, and migration assays under Nrf2 inhibition.ResultsA total of 113 major metabolites were identified in mZJP. Our findings revealed that mZJP alleviated retinal pathological alterations and inhibited EMT progression. Furthermore, mZJP upregulated Nrf2 and HO-1 expression levels while downregulating Akt and GSK-3β phosphorylation levels. Notably, the EMT-suppressing effect of mZJP was significantly attenuated upon Nrf2 silencing, as evidenced by enhanced cell migration, decreased epithelial marker expression (E-cadherin), increased mesenchymal marker expression (vimentin and α-SMA), suppression of the Nrf2 pathway, and activation of the Akt/GSK3β pathway.ConclusionOur study suggested that RPE protection by mZJP against oxidative stress induced EMT through Nrf2 activation and inhibition of the Akt/GSK3β pathway. MZJP could be a potential candidate drug for the treatment of dry AMD.